Analisis Sistem Informasi Penjualan Tanaman Obat Berbasis Web Dengan Metode Pieces Framework - Rachman Komarudin - STMIK Nusa Mandiri Jakarta (LPPM Universitas Bina Sarana Informatika, 2017)
Abstract – Analysis of web based medicinal sales information systems is needed to identify the shortcomings and weaknesses of the system. The analytical method used in the process of medicinal sales information system analysis using PIECES analysis method. Based on the calculation results obtained that for the Performance domain with the average value of satisfaction is in the range 3.7 with the category